Presumed criminal: black youth and the justice system in postwar New York - Suddler, Carl (New York University Press, 2019)
Introduction. "The way I see it": reframing black youth and racial injustice -- "The child is never basically bad": creating crime through prevention -- "Margie's day": youth, race, and uprisings in wartime Harlem -- "Every generation has had the habit of going to the devil": constructions of a postwar delinquent -- "Beware of the cat on the corner": deconstructing a cycle of outrage -- "In all our Harlems": policing black youths through the war on crime -- Afterword. "Without a wrinkle in today": an ode to young forever